2021
DOI: 10.1155/2021/5525064
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of Sutured Scleral-Fixated Foldable Intraocular Lens Implantation: A Retrospective Study of 5-Year Follow-Up

Abstract: Purpose. To evaluate long-term outcomes and complications of sutured scleral-fixated foldable intraocular lens (IOL) implantation. Design. Retrospective study. Methods. Patients who underwent sutured scleral-fixated foldable IOL implantation using 10-0 polypropylene suture were followed up for at least 5 years at one Chinese tertiary hospital and two primary hospitals. Results. 52 eyes among 48 patients (35 male and 13 female) were evaluated. The mean age (years) was 50.27 ± 20.08 (range: 6 to 81). The mean po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…30,31 Other studies on scleral suturing of the IOL without the surrounding capsule have shown similar, lower or higher rates of suture breakage compared with our study, but most of these studies have a short follow-up or included fewer eyes. 10,11,15,32,33 Yu et al observed no suture breakage in their study with a minimum of 5 years of follow-up, but they only included 52 eyes. 33 Studies by Luk et al and Kokame et al had larger sample sizes, and the frequency of suture breakage was 1.9% (n = 104) and 0.47% (n = 118), respectively, although with considerable variation in follow-up.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…30,31 Other studies on scleral suturing of the IOL without the surrounding capsule have shown similar, lower or higher rates of suture breakage compared with our study, but most of these studies have a short follow-up or included fewer eyes. 10,11,15,32,33 Yu et al observed no suture breakage in their study with a minimum of 5 years of follow-up, but they only included 52 eyes. 33 Studies by Luk et al and Kokame et al had larger sample sizes, and the frequency of suture breakage was 1.9% (n = 104) and 0.47% (n = 118), respectively, although with considerable variation in follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…10,11,15,32,33 Yu et al observed no suture breakage in their study with a minimum of 5 years of follow-up, but they only included 52 eyes. 33 Studies by Luk et al and Kokame et al had larger sample sizes, and the frequency of suture breakage was 1.9% (n = 104) and 0.47% (n = 118), respectively, although with considerable variation in follow-up. 11,32…”
Section: Discussionmentioning
confidence: 93%
“…IOL implantation in the sulcus with and without optic capture has the lowest complication rate and best visual acuity outcome [ 27 ]. Scleral fixation is often used in complex or traumatic cases without adequate capsule support, when other options are not feasible [ 28 , 29 ]. Iris-claw lenses have gained more and more popularity over the last years with the advantages of small learning curve and low complication rates [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu and Maxwell observed favorable longer-term findings and few complications after sutured scleral-fixated foldable lens implantation. Their procedure is safe, does not need complex equipment and can correct aphakia in the absence of adequate capsule support [29,30].…”
Section: Discussionmentioning
confidence: 99%